2016
DOI: 10.21873/anticanres.11089
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-324 in Human Cancer: miR-324-5p and miR-324-3p Have Distinct Biological Functions in Human Cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that have crucial regulatory functions in carcinogenesis. miR-324-5p and miR-324-3p are generated from the same hairpin RNA structure, however, both are diverse in their direct target genes and expression levels. We report that expression of miR-324-5p and -3p was frequently observed to be either up-regulated or down-regulated, and the selection preference of miR-324 for 5p and 3p arms significantly varied in various types or human cancer. Overexpression of miR-324-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 17 publications
(20 reference statements)
3
54
0
1
Order By: Relevance
“…In fact, this difference was not surprising because TCGA analysis was not always consistent with the experimental data. And the similar inconsistency between TCGA analysis and the experimental results had been reported before, which indicates that large numbers of samples or more patient cohorts are possibly helpful to further verify the prognostic role of Dyrk3 in HCC patients in future studies.…”
Section: Discussionsupporting
confidence: 60%
“…In fact, this difference was not surprising because TCGA analysis was not always consistent with the experimental data. And the similar inconsistency between TCGA analysis and the experimental results had been reported before, which indicates that large numbers of samples or more patient cohorts are possibly helpful to further verify the prognostic role of Dyrk3 in HCC patients in future studies.…”
Section: Discussionsupporting
confidence: 60%
“…Since miR-3163, miR-324-5p and miR-532-3p were the top three upregulated miRs shown by qPCR validation assay and the relationship of miR-3163/miR-324-5p to cancer were reported [8, 19, 20], we chose to study the role of miR-532-3p in the anti-cancer role of 20(S)-Rg3. We reported that 20(S)-Rg3 inhibited the Warburg effect in the ovarian cancer cells [10].…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that 20(S)-Rg3, one of the bioactive extracts from ginsenosides, reversed the vicious phenotype of ovarian cancer cells partly via inhibiting the Warburg effect [8, 9]. The preliminary study has found that 20(S)-Rg3 inhibits the Warburg effect via STAT3/HK2 pathways [10].…”
Section: Introductionmentioning
confidence: 99%
“…5 However, both the 5p and 3p mature variants have been reported to be differentially expressed in various cancers, and their expressions have been associated with both tumor suppressor and oncogenic functions. 5,13,14 This observation is supported by evidence that different mature miRNAs, cleaved from the 5# or 3# arms of the same stem-loop pre-miRNA, can be independently functional and have different targets. 10 In addition, the 5p/3p pairs can be differentially expressed from tissue to tissue, indicating that their expression might have tissue-dependent regulatory roles.…”
Section: Introductionmentioning
confidence: 80%